A novel polymer/ceramic composite film for different optical applications: optical linear, nonlinear, and limiting properties. (1st March 2021) - Abdel-Aziz, M M; Algarni, H; Ali, H Elhosiny; Yahia, I S; Khairy, Yasmin; Zahran, H Y; Abdellahi, M O; Al-Hagan, O; Solyman, S
Abstract: New composite films based on ceramic/polymeric matrix materials were synthesized using facile casting procedures for different optical devices. Herein, the composite comprises a semi-crystalline polymer (Polyvinyl alcohol, PVAL) embedded with various weight percentages of PbTiO3 . The structure and surface morphology change of PVAL were studied via XRD (Diffraction of x-ray) and SEM (Microscopy of Scanning Electron) analysis. The interactions between PVAL and PbTiO3, via the matrix's hydroxyl group, demonstrate a significant reduction in polymer crystallinity. Different parameters, such as internal strain, dislocation density, and crystallite size, were estimated from the XRD Gaussian fitting. SEM images show that the particles' agglomeration increased on the composite's surface with the doping ratio, which can influence the PVAL optical properties. The energy of the bandgap is estimated using absorption fitting and Tauc's relations. Nonlinear and refractive indices parameters- energy gap relations were studied. The nonlinear parameters χ (3) and n 2 increased with rising the percentage of PbTiO3 in the PVAL matrix from 0.935 × 10 −12 esu to 1.978 × 10 −12 esu, and 1.67 × 10 −11 esu to 3.29 × 10 −11 esu. Moreover, the high-frequency dielectric ( ε ∞ ) changes from 4.421 to 5.125. The behavior of optical limiting for the composites shows a decrease of He-Ne and green laser power. The present results indicate that the polymeric/ceramic films can be promising materials for laser CUT-OFF, optical fibers, and micro-optics applications.